2011
DOI: 10.1080/09537287.2011.627655
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable collaborative supply networks in the international clothing industry: a comparative analysis of two retailers

Abstract: Collaborative supply networks in the international clothing industry are of major economic significance in many countries, particularly in developing economies. The sector has gone through substantial changes in the last decade with the abolition of trade barriers and the increasingly dominant position of major retailers and brand owners in supply networks. The sustainability of clothing supply networks is subject to increasing public scrutiny. In this work, the characteristics and operation of collaborative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 32 publications
1
46
0
3
Order By: Relevance
“…This seems to be key too shedding light on the non-transparent textile/apparel supply chain and to making more representative propositions. [73] x 0 x MacCarthy & Jayarathne [91] 0 0 0 Baskaran et al [98] 0 0 0 Anner [68] x x x Miller & Williams [78] x 0 0 Locke et al [72] x 0 0 Yu [80] x 0 x Hoang & Jones [89] 0 0 x Mamic [94] 0 x 0 Perry & Towers [4] x 0 0 Huq et al [45] x 0 x Auchter [87] x x x Krueger [88] x x 0 Gupta & Hodges [81] x 0 x Posthuma & Bignami [70] x 0 0 Stigzelius & Mark-Herbert [74] x 0 x Baskaran et al [102] 0 0 0 Jiang et al [79] x 0 x TOTAL 27 16 16 Appendix C Table C1. Forty-five relevant papers appearing in focal company categories.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This seems to be key too shedding light on the non-transparent textile/apparel supply chain and to making more representative propositions. [73] x 0 x MacCarthy & Jayarathne [91] 0 0 0 Baskaran et al [98] 0 0 0 Anner [68] x x x Miller & Williams [78] x 0 0 Locke et al [72] x 0 0 Yu [80] x 0 x Hoang & Jones [89] 0 0 x Mamic [94] 0 x 0 Perry & Towers [4] x 0 0 Huq et al [45] x 0 x Auchter [87] x x x Krueger [88] x x 0 Gupta & Hodges [81] x 0 x Posthuma & Bignami [70] x 0 0 Stigzelius & Mark-Herbert [74] x 0 x Baskaran et al [102] 0 0 0 Jiang et al [79] x 0 x TOTAL 27 16 16 Appendix C Table C1. Forty-five relevant papers appearing in focal company categories.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the usual case is that these buyers pass on pressures to their suppliers to be compliant with local, national, and international laws, as well as labor standards and a company's code of conduct. This has been mentioned by nine papers [67,71,91]. Stigzelius and Mark-Herbert [74] interviewed factory managers in India and found that the implementation of the SA8000 standard is strongly required by western buying firms.…”
Section: Driversmentioning
confidence: 99%
See 3 more Smart Citations